1982
DOI: 10.1093/jn/112.12.2279
|View full text |Cite
|
Sign up to set email alerts
|

Balance and Tissue Distribution of Vanadium after Short-Term Ingestion of Vanadate

Abstract: Forty-six female Sprague-Dawley rats (170-200 g) were randomly assigned to one of six treatment groups receiving 0.1, 5.0, or 25.0 ppm dietary vanadium with either normal (0.13 mEq/g) or high (1.82 mEq/g) dietary potassium. Supplemental vanadium was administered as sodium metavanadate. These diets were fed for 2 weeks, and all feces and urine collected. At the end of the treatment period, brain, liver, renal cortex and medulla, whole blood, and plasma were obtained and analyzed for vanadium by atomic absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…The carrier-added, direct comparison study between 48 V-BMOV and 48 VOSO 4 [104] demonstrated a similar pattern of biodistribution to that of inorganic vanadium salts observed earlier [33,97,98,[139][140][141], especially with regard to the order of relative accumulation, with bone > kidney > liver. A long half-life of elimination (>10 d for 48 V in bone after a one-time 10 lM dose by oral gavage in rats) and low level of absorption (with bone retaining $0.1% of an oral dose/g tissue 24 h after an oral dose of VOSO 4 ), were corroborated for VOSO 4 in the carrier added study [104], and shown to be enhanced by BMOV, which had a two-fold longer half-life of elimination from bone.…”
Section: Bmov/beov Pharmacokineticssupporting
confidence: 63%
See 1 more Smart Citation
“…The carrier-added, direct comparison study between 48 V-BMOV and 48 VOSO 4 [104] demonstrated a similar pattern of biodistribution to that of inorganic vanadium salts observed earlier [33,97,98,[139][140][141], especially with regard to the order of relative accumulation, with bone > kidney > liver. A long half-life of elimination (>10 d for 48 V in bone after a one-time 10 lM dose by oral gavage in rats) and low level of absorption (with bone retaining $0.1% of an oral dose/g tissue 24 h after an oral dose of VOSO 4 ), were corroborated for VOSO 4 in the carrier added study [104], and shown to be enhanced by BMOV, which had a two-fold longer half-life of elimination from bone.…”
Section: Bmov/beov Pharmacokineticssupporting
confidence: 63%
“…2 for current rendition) [14]. Pharmacokinetic analyses predicted that most of an inorganic vanadium dose would be excreted rapidly, having never been absorbed at all [96][97][98]. Thus, an apparent overlap between toxic and therapeutic doses disappeared.…”
Section: Dose Dependence? Dichotomy Of Responsementioning
confidence: 99%
“…In rats, the renal cortex accumulated the highest, and the brain the lowest concentrations of vanadium (Bogden et al 1982). In goats with high (2000 mg Vkg À1 ) and low (< 20 mg V kg À1 ) vanadium contents in the feed DM, all organs analyzed reflected the different vanadium intakes significantly.…”
Section: Distributionmentioning
confidence: 94%
“…Uptake of radioactive vanadium pentoxide (V 2 O 5 ) given orally to rats was 2.6% of the administered dose (Conklin et al, 1982). Other studies in rats have indicated that amounts greater than 10% can be absorbed from the gastrointestinal tract under some conditions (Bogden et al, 1982;Wiegmann et al, 1982).…”
Section: Absorption Distribution Metabolism and Excretionmentioning
confidence: 99%